Household willingness-to-pay for smart home functionalities in Singapore - Low, Nicole Ni Qi (2016)
In light of the Smart Nation vision of Singapore, this paper attempts to establish the willingness-to-pay for different types of Smart Home functionalities among Singaporean households in 2016 and analyses the factors that affects households’ investment decision in Smart Home. Data were collected through household surveys with the adoption of the close-ended contingent valuation method. The results suggest that households generally have a positive view toward the Smart Home concept. With the exception of the automation functionality, households have willingness-to-pay at least as high as the current market prices for display and remote access functionalities. Age, gender, household income and environmental awareness also determine a household’s willingness to invest in Smart Home functionalities. In addition, foreseeable concerns need to be addressed before a market penetration is viable.